Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pada Pt. Mahakam Berlian Samjaya Samarinda - Noval Aditya; Fandi Kharisma (Borneo Student Research (BSR), 2022)
ABSTRACT The purpose of this study was to determine "How much influence the work environment and work stress have on employee performance at PT. Mahakam Berlian Samjaya Samarinda. In this study, the independent variables are Work Environment (X1) and Job Stress (X2), while the dependent variable is Employee Performance (Y). This type of research is a quantitative research analyzed using statistics. The number of samples obtained by using a saturated sample that is to make the entire population of employees of PT. Mahakam Berlian Samjaya Samarinda became a sample of 98 respondents. The data was collected using a questionnaire while the data analysis was carried out using multiple regression analysis. Data were collected using a questionnaire that had been tested for validity (CFA) and reliability (Cronbach Alpha). Multiple linear regression analysis was used to test the hypothesis of this study. The results of this study indicate that: (1) The coefficient of determination (R2) of the work environment and work stress on employee performance has an R square (R2) is 0.511 or 51.1%. (2) In the F (simultaneous) test, the calculated F is 49.671 this value is greater than the F table, namely 3.09 or F arithmetic > 3.09 with a probability of 0.000. Because the probability value is much smaller than 0.05, it can be interpreted that both work environment variables and work stress simultaneously have a significant effect on employee performance. (3) t test (partial) Work environment variable has a value of t count > t table (4,089 > 1,661) or Sig. t < = 0.000 < 0.05, then H1o is rejected and H1a is accepted, meaning that there is a significant effect of the Work Environment on Employee Performance. (4) t test (partial) Work stress variable has a t count > t table (1,920 > 1,661) or Sig. t > = 0.058 <0.05, then H2o is accepted and H2a is rejected, meaning that there is a non-significant effect of work stress on employee performance. (5) Work Environment is the dominant variable or the biggest in influencing employee performance at PT. Mahakam Berlian Samjaya Samarinda. Keywords: Work Environment, Work Stress, Employee Performance